Respuesta :

Answer:

They got 12 by multiplying 3 × 4

Step-by-step explanation:

They used distributive property to multiply the 3 by each number in the parentheses

3 × x/3 = 1x = x

3 × 4 = 12

x + 12 = 6 × 3

They mutliplied 6 × 3 to get 18

x + 12 = 18

They then subtracted both sides by 12 to isolate the variable

x + 12 - 12 = 18 - 12

x = 6

Answer:

hope this helps! lmk if you still dont understand it!

:)

Step-by-step explanation:

you do 3*4 which gives you 12 and 3*x/3, but you should keep it as x

6*3 is 18

x+12=18 (solve for x)

-12=-12

x=6

check the answer:

3*(6/3+4)=6*3

3(2+4)=6*3

6+12=6*3

18=18

ACCESS MORE